Prevalence of Thyroid Dysfunction Among Greek Type 2 Diabetic Patients Attending an Outpatient Clinic - Papazafiropoulou, Athanasia (Elmer Press, 2010)
BACKGROUND: The aim of the present study was to determine the prevalence of thyroid dysfunction in patients with type 2 diabetes (T2D) attending an outpatient clinic. METHODS: We examined thyroid dysfunction in a total of 1,092 patients with T2D. RESULTS: Prevalence rate of thyroid dysfunction was 12.3%. In the group with thyroid dysfunction there was an excess of females in comparison with the group without thyroid dysfunction (P < 0.001). In addition, patients with thyroid dysfunction had higher values of body mass index (P = 0.03) and HDL-cholesterol levels (P = 0.01), and lower values of LDL-cholesterol levels (P = 0.001) in comparison with patients without thyroid dysfunction. Multivariate analysis demonstrated that presence of thyroid dysfunction was related with gender (OR: 0.220, 95% CI: 0.141 - 0.352) and LDL-cholesterol levels (OR: 0.990, 95% CI: 0.985 - 0.995). CONCLUSIONS: The prevalence of thyroid dysfunction among Greek diabetic patients is 12.3%. Diabetic women were more frequently affected than men. Presence of thyroid dysfunction was associated with lower levels of LDL-cholesterol concentrations. KEYWORDS: Type 2 diabetes mellitus; Thyroid dysfunction; Hypothyroidism; Gender; LDL-cholesterol; Greece